Analisis Daya Dukung Pondasi Tiang Bored Pile Pada Proyek Morrissey - Ikhsan, Ayie Maulana; Alizar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The foundation is the lowest structural component of a building. All the load of the building is supported by the foundation. transferring the load to the soil below. Shallow foundations and deep foundations are two categories of foundations. The Morrissey hotel project uses bored pile foundation, as bored pile foundation is used for buildings in densely populated areas. Bored pile foundation is done by using a drilling machine to drill a hole of a certain depth, then filled with cast concrete and iron bones. This technique is considered to produce a foundation with good durability, especially over a long period of time. Various techniques in bored pile calculation, including conus penetration test (CPT), standard penetration test (SPT), and assessment based on soil shear strength characteristics such as cohesion (c), inner shear angle (?), and soil content weight (?), can be used to determine the bearing capacity of bored piles. The tip bearing capacity (Qb) and the blanket friction bearing capacity (????????), which are determined using the formula, are the two main parts of the bored pile axial bearing capacity.